IMPLEMENTASI MEDIA PERMAINAN ULAR TANGGA DALAM PEMBELAJARAN IPA DI SD PADA SISTEM PERNAPASAN MANUSIA - Albertus Kristianta Wicaksana; Ana Fitrotun Nisa; Insanul Qisti Bariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study employs a qualitative method with a descriptive approach to evaluate the effectiveness of using snakes and ladders as an educational medium in teaching human respiration to 5th-grade students in elementary school. The main focus of the research is to respond to the direct experiences of students in learning human respiration through a game-based approach. Through participatory observation, tests, and structured interviews, data were collected for thematic analysis to explore the impact and experiences of students using the game as a learning tool. The results show that the snakes and ladders game stimulates active engagement, increases interest in learning, and strengthens the understanding of human respiration concepts. Additionally, the game promotes positive social interaction and teamwork in solving learning challenges. These findings offer new insights into the benefits of innovative and engaging learning approaches in teaching science at the elementary school level, which can enrich students' learning experiences and strengthen their understanding of complex subject matter. Keywords: Educational media, snakes and ladders game, human respiration, qualitative approach, descriptive approach, elementary students.